Effects of non-dominant side training on athletic performance: a systematic review - Zhang, Yugang; Jin, Chengye; Sun, Min; Zhang, Lei (Frontiers in Physiology, 2025)
Evidence suggests that non-dominant side training benefits athletic performance. However, there is a lack of systematic reviews on the effects of non-dominant side training on athletes’ performance. This study aims to synthesize existing research on the impact of non-dominant side training on athletic performance. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, a systematic search was conducted on 16 June 2024, across the VIP Database, PubMed, Web of Science Core Collection, EBSCOhost, and CINAHL Plus. The search strategy adhered to the PICOS framework and included a combination of keywords related to non-dominant side training, athletic performance, and experimental studies. After screening 269 identified studies, nine studies were included in this systematic review. The included studies were evaluated using the PEDro scale, with a mean score of 4.22, indicating moderate methodological quality. Analysis of the selected studies revealed that a total of 359 athletes aged 12–24 years participated in non-dominant side training interventions. The intervention durations ranged from 8 weeks to 16 months, with training frequencies varying from once to four times per week. The findings demonstrated significant effects of non-dominant side training on athletic technique, strength, change-of-direction speed, jumping ability, balance, and mental rotation tasks. Furthermore, the results indicate that non-dominant side training has a significant impact across different sports disciplines and age groups. These findings provide evidence-based training strategies to optimize athletic performance in various sports.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, Identifier CRD42024551710.